Impact of Performance Status on Response and Survival Among Patients Receiving Checkpoint Inhibitors for Advanced Solid Tumors. Issue 1 (January 2022) - Krishnan, Mridula; Kasinath, Pooja; High, Robin; Yu, Fang; Teply, Benjamin A.
Abstract : PURPOSE: Clinical trials, which led to the approval of immune checkpoint inhibitors (ICI), have been almost exclusively performed in patients with good Eastern Cooperative Oncology Group performance status (ECOG PS of 0-1). However, ICI remains an attractive option for patients with advanced tumors and poor PS. We hypothesized that patients with ECOG PS ≥ 2 would have worse outcomes with ICI. METHODS: We retrospectively identified patients with advanced solid tumors who were treated with ICI at our institution. The log-rank test compared the survival among patients with different ECOG PS. We used a proportional hazards model to assess association between ECOG PS and overall survival (OS) with adjustment for covariates including age, sex, malignancy type, time from advance disease diagnosis, and line of therapy. We compared overall response rates between groups with Pearson chi-square exact test. We also analyzed in-hospital mortality and hospice referral rates. RESULTS: We identified 257 patients treated with ICI. One hundred eighty-two patients had ECOG PS 0-1, and 75 had ECOG PS ≥ 2. The median overall survival was 12.6 months for the ECOG PS 0-1 group compared with 3.1 months for the ECOG PS ≥ 2 group ( P < .001). The overall response rate for patients with ECOG PS 0-1 was 23% compared with 8% for those with poor PS ( P = .005). Patients with poor PS treated with ICI had similar hospice referral rates (67% for ECOG PS ≥ 2 v 61.9% for ECOG PS 0-1, P = .50) but were more likely to have in-hospital death as compared with the good PS group (28.6% v 15.1%, P = .035). CONCLUSION: Despite the appeal of ICI in patients with advanced malignancy and poor PS, outcomes in this cohort were poor. Prospective trials defining the activity and role of ICI in poor PS are urgently needed.